Psychobiosocial states in competitive badminton: Similarities and differences between juniors, adolescents and adults. - Chia-Smith, Y.-D. (International Journal of Racket Sports Science, 2019)
Emotions affect the way elite athletes respond during competitive play. Elite athletes who identify and regulate emotions can increase their consistency and optimize high quality play. This cross-sectional study examined the extent to which psychobiosocial states of elite badminton players vary by age. Ninety-one elite badminton players in three age groups (lower juniors, upper juniors, and adults) rated their post-play perceptions on eight components of psychobiosocial states (Bortoli, et al., 2008) for both their best and worst performance during the tournament. Descriptive statistics assessed the relative strength of emotions on each item and an analysis of variance examined differences between the three groups. Age differences were found in the perception of the psychobiosocial states in competitive badminton matches in terms of most identified states and intensity. The findings inform coaches` understanding athlete`s individual zone of optimal function (IZOF) and can help them cope with psychobiosocial states during matches.